MEASURING THE IMPACT OF SOME FISCAL POLICY VARIABLES ON THE BALANCE OF PAYMENTS IN IRAQ FOR THE PERIOD (2004-2021) (World Economics and Finance Bulletin, 2022)
The research aims to identify the performance of some fiscal policy variables and the balance of payments in Iraq, and to identify the impact of the fiscal policy variables on the balance of payments through the use of the analytical descriptive approach and the quantitative approach. To achieve this goal, an annual time series extending from (2004-2021) was used, and the (ARDL) model was used to estimate the short-term relationship and to know the cointegration relationship using the (Bound test) methodology between the variables of fiscal policy (revenues, expenditures) and the balance of payments, and then estimating the long-term relationship between variables. Through the results of the tests, the research concluded that there is a positive effect and an insignificant effect of the fiscal policy variables that were used, while the positive effect was for the public revenue variable, as its impact on the balance of payments in Iraq was (22.4) in the short term and (8.5) in the long term. The non-existent was for public expenditures, as it does not affect the balance of payments in the short and long term, because its probability was greater than 5%. The research recommends that the use of fiscal policy tools is supposed to be carefully studied and to avoid randomness and improvisation in making decisions regarding revenues and public expenditures to ensure maximum benefit from public expenditures in the service of the Iraqi economy and society by rationalizing their use and tabulating their expenditure items
Keywords: Fiscal Policy; Balance of Payments; Public Expenditures